EtMIC3 and its receptors BAG1 and ENDOUL are essential for site-specific invasion of Eimeria tenella in chickens - Li, Wenyu (Vet Res, 2020)
Avian coccidian parasites exhibit a high degree of site specificity in different Eimeria species. Although the underlying mechanism is unclear, an increasing body of evidence suggests that site specificity is due to the interaction between microneme proteins (MICs) and their receptors on the surface of target host cells. In this study, the binding ability of E. tenella MICs (EtMICs) to different intestinal tissue was observed by immunofluorescence to identify the key surface molecule on the parasite responsible for the site specificity. Subsequently, we identified the corresponding host-cell receptors by yeast two-hybrid screening and glutathione-S-transferase pull-down experiments and the distribution of these receptors was observed by immunofluorescence in chicken intestinal tissues. Finally, we evaluated the efficacy of receptor antiserum against the infection of E. tenella in chickens. The results showed that EtMIC3 could only bind to the caecum while EtMIC1, EtMIC2, and EtAMA1 did not bind to any other intestinal tissues. Anti-serum to EtMIC3 was able to block the invasion of sporozoites with a blocking rate of 66.3%. The receptors for EtMIC3 were BCL2-associated athanogene 1 (BAG1) and Endonuclease polyU-specific-like (ENDOUL), which were mainly distributed in the caecum. BAG1 and ENDOUL receptor antiserum reduced weight loss and oocyst output following E. tenella infection, showing partial inhibition of E. tenella infection. These data elucidate the mechanism of site specificity for Eimeria infection and reveal a potential therapeutic avenue.